Do digital technologies influence the relationship between the COVID-19 crisis and SMEs' resilience in developing countries? - Afef Khalil; Mohammed El Amine Abdelli; Emmanuel Mogaji (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The COVID-19 pandemic is not only a medical emergency but also a business emergency that has created the need for organizations to be resilient and versatile in managing the impact of the pandemic on their business operations. At this time, small- and medium-sized enterprises (SMEs) are the most vulnerable to the economic disaster caused by the recent crisis, because these companies do not have the necessary resources to absorb losses. This research reviewed the impact of digital technologies on SMEs' resilience during the pandemic, focusing on companies in developing countries. Based on the 96 SMEs surveyed across six developing countries, the study shows that digital technology has helped SMEs to survive the pandemic, assisting SMEs in becoming more robust and ensuring their survival. This research fills a significant research gap in the literature, highlighting the inherent challenges of SMEs in developing countries and their digital transformation strategies. This study also offers practical recommendations for SMEs, tech developers, and policymakers to invest more effort in putting new procedures in place to ensure the efficacy of digital technology.
Keywords: 650; COVID-19; developing countries; digital technology; resilience; small- and medium-sized enterprises